Comparison of usefulness between the Mini-Balance Evaluation Systems Test and the Berg Balance Scale for measuring balance in patients with subacute stroke: a prospective cohort study - Inoue, Seigo; Takagi, Hideyuki; Tan, Emiko; Oyama, Chisato; Otaka, Eri; Kondo, Kunitsugu; Otaka, Yohei (Frontiers in Rehabilitation Sciences, 2024)
Introduction The aim of this study was to compare the clinical applicability of the Mini-Balance Evaluation Systems Test and the Berg Balance Scale for measuring balance in inpatients with subacute stroke. Methods This was a prospective observational study which included 58 consecutive patients admitted to a convalescent rehabilitation hospital with a first-ever stroke and who met the inclusion/exclusion criteria. The Mini-Balance Evaluation Systems Test and the Berg Balance Scale were used to assess patient balance at admission and discharge. The ceiling and floor effects and responsiveness of each balance score were examined. In addition, receiver operating characteristic analysis based on each balance score at admission was used to examine its discriminative power to predict ambulatory independence and falls during hospitalization. Results The mean (standard deviation) change between admission and discharge for each balance scale was 4.4 (4.7) for the Mini-Balance Evaluation Systems Test and 8.3 (10.0) for the Berg Balance Scale, with standard response means, a measure of responsiveness of 0.9 (large) and 0.8 (medium), respectively. Each balance score at admission almost equally predicted gait independence and fallers during hospitalization. On the contrary, only the distribution of scores on the Berg Balance Scale at discharge showed a ceiling effect, with 25 patients (43%) obtaining a perfect score. Discussion The Mini-Balance Evaluation Systems Test may be useful as a balance measure for inpatients with subacute stroke because it is less susceptible to ceiling effects and more responsive than the Berg Balance Scale.